Secular and Cross-Section Industrialization Patterns: Some Further Evidence on the Kuznets-Chenery Controversy - Gregory, Paul; Griffin, James M. (The Review of Economics and Statistics, 1974)
INFORMATION on patterns of structural change during modern economic growth is summarized in Kuznets (1967 and 1971). The use of secular data to identify such patterns, however, must be limited, for relatively few countries have compiled suitable long-term records. Thus, attention has focused upon an alternative data source, namely, intercountry data for evidence on past and future trends in industrial structure (Temin, 1967; Kuznets, 1967, pp. 431-436; Chenery-Taylor, 1968, p. 391; Houthakker, 1965, p. 277). Despite the frequent use of cross sections to infer intertemporal patterns, relatively little empirical and theoretical work has been devoted to the interpretation of cross-section patterns vis-a-vis intertemporal patterns. Exceptions to this rule are Kuh (1959), Houthakker (1965), Temin (1967), Maizels (1963), Kuznets (1971, chapter. 4), and Chenery-Taylor (1968). The strikingly different results obtained by Kuznets (1971) and Chenery-Taylor (1968) concerning the compatibility of intercountry versus intertemporal patterns raise the basic issue which this study addresses.'